« A Flight », de Charles Dickens (1851), récit de voyage ? - Isabelle Hervouet-Farrar (Cahiers Victoriens et Edouardiens)
This paper is centred on « A Flight », an article published by Dickens in Household Words in 1851, the narrative of a train journey from London to Paris. Dickens’s article is published today by Penguin both as a piece of journalism (in Selected Journalism) and as a piece of fiction (in Selected Short Fiction), which raises the question of the genre(s) to which it belongs. This paper aims at showing that far from being a classic travel narrative offering a modicum of objectivity, « A Flight » shows us how fiction is created when a hyper-active narrator uses every exterior detail as a pretext to the expression of his creative energy. In Dickens’s text, the aim of the train journey, France, is portrayed as a fictional place where imagination can truly express itself and even run wild.